Quantitative posture analysis of 2D, 3D, and optical microscope visualization methods for microsurgery tasks. - Soares, Marcelo M.; Jacobs, Karen; Yu, Denny; Sackllah, Michael; Woolley, Charles; Kasten, Steven; Armstrong, Thomas (Work)
The purpose of this paper is to present a quantitative posture analysis of microsurgery tasks performed with different visualization methods. Microsurgery is traditionally performed using a binocular microscope; however surgeons are constrained by the optical eyepieces and are forced to assume joint angles that deviate away from neutral postures. This may be especially problematic for the neck and can increase surgeon discomfort and fatigue. Alternative visualization methods may improve surgeon posture by eliminating the constraints imposed by the microscope. This study examines both 2D and 3D heads-up displays as possible alternatives. Six subjects performed microsurgical tasks with each visualization methods for four hours. Quantitative posture analysis was done using Maxtraq software that tracks reflective markers on the subjects. The initial analysis of neck, upper arm, and elbow angles found significant differences between each display. A biomechanical analysis found that the differences in angles can result in loads on the neck joint that are twice as high in the microscope than the headsup displays. Although the alternative displays can result in better postures, improvements the display technology is needed to improve microsurgical task performance.